The battle for children : World War II, youth crime, and juvenile justice in twentieth-century France - Fishman, Sarah, 1957- (Harvard historical studies, 2002)
The Battle for Children links two major areas of historical inquiry: crime and delinquency with war and social change. In a study based on impressive archival research, Sarah Fishman reveals the impact of the Vichy regime on one of history's most silent groups - children - and offers enlightening new information about the Vichy administration. Fishman examines how French children experienced the events of war and the German occupation, demonstrating that economic deprivation, not family dislocation, sharply drove up juvenile crime rates. Wartime circumstances led authorities to view delinquent minors as victims, and provided the opportunity for reformers in psychiatry, social work, and law to fundamentally transform France's punitive juvenile justice system into a profoundly therapeutic one. Vichy-era legislation thus formed the foundation of the modern juvenile justice system in France, which rarely incarcerates delinquent youth. In her examination of the critical but unexpected role the war and the authoritarian Vichy regime played in the transformation of France's juvenile courts and institutions, Fishman has enriched our knowledge of daily life in France during World War II, refined our understanding of Vichy's place in the historical development of France, and provided valuable insights into contemporary debates on juvenile justice. --